Perspective Plan for Coastal Andhra Volume-I Resource Inventory - Planning Commission (Planning Commission, 1974)
The rocks of the Coastal Andhra consist for the most part of the members of the oldest rock system, the "Archaean"—which include schists, granites and other crystalline and metamorphic types. These ancient rocks are exposed over the greater part of the ridges of the Eastern Ghats of Srikakulam and Visakhapatnam districts, the uplands of the West Godavari and the ghat ridges of the interior agency of East Godavari often attaining high elevations overlooking river Godavari ; parts of Guntur, Prakasam and Nellore districts.
Planning and Co-operation Department Andhra Pradesh